Credit where it is due - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
In Spore N 12, Dr Mohammed Yunus, described how the founding of the Grameen Bank in Bangladesh had helped to stimulate the very poor to develop self-reliance through group credit and the setting up of small business enterprises. The UN...